Pengaruh Penerapan E-Commerce dan Literasi Keuangan Terhadap Kinerja Pelaku Ekonomi Kreatif Subsektor Fashion dan Kriya di Bojonegoro - Nyiwa Zumrotul Khasanah; Jeni Susyanti; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study was conducted to determine the effect of the application of e-commerce and financial literacy on the performance of creative economy actors in the fashion and craft sub-sector in Bojonegoro. This research uses explanatory research and quantitative approach. Sugiyono's theory, the method used to find the number of samples in this study is to use the Slovin formula and it is known that the number of samples is 85 respondents.To solve the problem in this research, using validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classic assumption test. This study uses multiple linear regression analysis with the help of SPSS 20. The results of this study are that there is a simultaneous influence between E-Commerce and Financial Literacy on the Performance of Creative Economy Actors in the Fashion and Craft Subsectors in Bojonegoro, E-commerce Variables affect the Performance of Actors Creative Economy Creative Economy Actors Fashion and Craft Sub-sector in Bojonegoro, Financial Literacy Variables affect the Performance of Creative Economy Actors Fashion and Craft Sub-sector Creative Economy Actors in Bojonegoro. Keywords: Creative economy performance, E-commerce, Financial Literacy